The effects of visceral obesity and androgens on bone: trenbolone protects against loss of femoral bone mineral density and structural strength in viscerally obese and testosterone-deficient male rats. Issue 3 (March 2016) - Donner, D.; Elliott, G.; Beck, B.; Forwood, M.; Toit, E.
Abstract Summary In males, visceral obesity and androgen deficiency often present together and result in harmful effects on bone. Our findings show that both factors are independently associated with adverse effects on femoral bone structure and strength, and trenbolone protects rats from diet-induced visceral obesity and consequently normalises femoral bone structural strength. Introduction In light of the rapidly increasing incidence of obesity and osteoporosis globally, and recent conjecture regarding the effects of visceral adiposity and testosterone deficiency on bone health, we investigated the effects of increased visceral adipose tissue (VAT) mass on femoral bone mineral density (BMD), structure and strength in normal weight rats with testosterone deficiency. Methods Male Wistar rats (n = 50) were fed either standard rat chow (CTRL, n = 10) or a high-fat/high-sugar diet (HF/HS, n = 40). Following 8 weeks of feeding, rats underwent sham surgery (CTRL, n = 10; HF/HS, n = 10) or orchiectomy (HF/HS + ORX, n = 30). Following a 4-week recovery period, mini-osmotic pumps containing either vehicle (CTRL, n = 10; HF/HS, n = 10; HF/HS + ORX, n = 10), 2.0 mg kg day−1, testosterone (HF/HS + ORX + TEST, n = 10) or 2.0 mg kg day−1 trenbolone (HF/HS + ORX + TREN, n = 10) were implanted for 8 weeks of treatment. Dual-energy X-ray absorptiometry and three-point bending tests were used to assess bone mass, structure and strength of femora. Results Diet-induced visceral obesity resulted in decreased bone mineral area (BMA) and content (BMC) and impaired femoral stiffness and strength. Orchiectomy further impaired BMA, BMC and BMD and reduced energy to failure in viscerally obese animals. Both TEST and TREN treatment restored BMA, BMC, BMD and energy to failure. Only TREN reduced visceral adiposity and improved femoral stiffness and strength. Conclusions Findings support a role for both visceral adiposity and testosterone deficiency as independent risk factors for femoral osteoporosis, adverse bone geometry and impaired bone strength in male rats. Trenbolone may be a more effective candidate for androgen replacement therapy than testosterone in viscerally obese testosterone-deficient males.